Structure-based optimization of type III indoleamine 2,3-dioxygenase 1 (IDO1) inhibitors - Ute F. Röhrig; Somi Reddy Majjigapu; Pierre Vogel; Aline Reynaud; Florence Pojer; Nahzli Dilek; Patrick Reichenbach; Kelly Ascenção; Melita Irving; George Coukos; Olivier Michielin; Vincent Zoete (Journal of Enzyme Inhibition and Medicinal Chemistry, 2022)
The haem enzyme indoleamine 2,3-dioxygenase 1 (IDO1) catalyses the rate-limiting step in the kynurenine pathway of tryptophan metabolism and plays an essential role in immunity, neuronal function, and ageing. Expression of IDO1 in cancer cells results in the suppression of an immune response, and therefore IDO1 inhibitors have been developed for use in anti-cancer immunotherapy. Here, we report an extension of our previously described highly efficient haem-binding 1,2,3-triazole and 1,2,4-triazole inhibitor series, the best compound having both enzymatic and cellular IC50 values of 34 nM. We provide enzymatic inhibition data for almost 100 new compounds and X-ray diffraction data for one compound in complex with IDO1. Structural and computational studies explain the dramatic drop in activity upon extension to pocket B, which has been observed in diverse haem-binding inhibitor scaffolds. Our data provides important insights for future IDO1 inhibitor design.